Host-cell reactivation of alkylated T7 bacteriophage - Lane, D; Mamet-Bratley, M D; Karska-Wysocki, B (Biochimica et biophysica acta, 1979)
Purified T7 phage, treated with methyl methanesulfonate, was assayed on Escherichia coli K-12 host cells deficient in base excision repair. Phage survival, measured immediately after alkylation or following incubation to induce depurination, was lowest on a mutant defective in the polymerase activity of DNA polymerase I (p3478). Strains defective in endonuclease for apurinic sites (AB3027, BW2001) gave a significantly higher level of phage survival, as did the strain defective in the 5'--3' exonuclease activity of DNA polymerase I (RS5065). Highest survival of alkylated T7 phage was observed on the two wild-type strains (AB1157, W3110). These results show that alkylated T7 phage is subject to repair via the base excision repair pathway.